Effect of Optical Feedback on the Modulation Properties of AlGaInP Semiconductor Laser - Musab Ahmed (College of Education for Pure Sciences, 2008)
Abstract Effect of optical feedback (O.F) on AlGaInP semiconductor laser properties and intensity modulation has been studied experimentally. Threshold current of semiconductor laser decreased 1mA when O.F equal to 160W , while there is no significant decreases observed in threshold current both when increasing O.F above that value or less than it. Influence of O.F on amplitude modulation spectrum at frequencies modulation (0.123,0.246, 0.546, 1.2)MHz has been studied. Fundamentals harmonic spectrum peaks increased with O.F especially at frequency modulation (1.2)MHz , whereas opposite effect of O.F observed on Fundamentals harmonic spectrum peaks at frequency 132kHz, since it decreased with O.F . O.F participate in decreasing of relative intensity noise (RIN) just at frequencies modulation(0.264, 0.546, 1.2)MHz with appearance of Flicker noise at frequency 132kHz. Signal to noise ratio (SNR) increased with O.F especially at frequency modulation equal to 1.2MHz has been observed.